Strategi Badan Usaha Milik Desa Dalam Mengembangkan Agrowisata Belimbing - Khasanah, Uswatun; Rodiyah, Isnaini (Public Policy, 2023)
This study aims to analyze and describe the BUMDes strategy in developing Belimbing Agrotourism in Watesari Village. This research uses a qualitative descriptive method. Data collection was carried out through observation, interviews and supporting documentation. The informants interviewed in this research were the Village Head, Village Government and Management of BUMDes Bina Sejahtera. The results of this study indicate that the BUMDes Strategy is reviewed from indicators according to Jack Kooten in Kasmira. The results of the four indicators are: 1) Corporate strategy, Organizational strategy The organizational strategy of BUMDes Bina Sejahtera has set goals and vision and mission in developing Agrotourism Belimbing. 2) Strategy program indicator, Agrotourism Belimbing in Watesari Village has offered three programs that still have shortcomings and have not been realized properly. 3) Resource Support Strategy indicator, seen from the aspect of human resources at BUMDes Bina Sejahtera in quality and quantity, it is still not fulfilled, the aspect of financial resources is still not fulfilled and are still being designed in the following year. 4) Institutional strategy, in terms of organizational structure BUMDes Bina Sejahtera has frmed management but is still not running optimally, in terms of partnerships BUMDes has not cooperated with third parties either form the private sector or from the goverment, but has collaborated with Watesari Village Youth and Local Residents in developing Agrotourism Belimbing Watesari.